A systematic review and meta-analysis of the effect of thymol as an anti-inflammatory and wound healing agent: A review of thymol effect on inflammation and wound healing - Gabbai-Armelin, Paulo R. [UNESP]; Sales, Luciana S. [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Oliveira, Analu Barros de [UNESP]; Oliveira, Juliana R. de [UNESP]; Giro, Elisa M. A [UNESP]; Brighenti, Fernanda L. [UNESP] (Wiley, 2022)
Thymol (THY) exhibits antibacterial and antioxidant properties. Recent studies have also shown that THY presents anti-inflammatory and healing properties. This review focused on in vitro and in vivo investigations related to THY utilization, as an anti-inflammatory and/or wound healing agent. PubMed, WebOfScience, and Scopus were examined. Independent reviewers conducted all diagram steps. PRISMA was followed for data extraction. RoB 2 and SYRCLE were utilized to assess the risk of bias for in vitro and animal studies. Meta-analysis was performed for in vitro and in vivo articles that investigated THY as an anti-inflammatory agent. Thirty-six and 15 articles were included in the qualitative analysis and meta-analysis, respectively. Studies showed high risk of bias related to sampling, allocation procedures, randomization, and blinding. Even so, for in vitro studies, significant result was observed for IL-2. For in vivo studies, significant results were found for IL-1, IL-17, TNF-α, AST, MPO, and CRP, with higher levels noticed in control groups. THY presents significant properties as anti-inflammatory, ameliorating affections of the digestive system, cardiovascular problems, respiratory system and dermal damages, and burns. Researches are needed to clarify THY dose–response relationship and its mechanism of action, especially in the application of THY as a healing agent.
Keywords: anti-inflammatory; meta-analysis; monoterpene; systematic review; thymol; wound healing